2020
DOI: 10.1002/lno.11405
|View full text |Cite
|
Sign up to set email alerts
|

Different carboxyl‐rich alicyclic molecules proxy compounds select distinct bacterioplankton for oxidation of dissolved organic matter in the mesopelagic Sargasso Sea

Abstract: Marine dissolved organic matter (DOM) varies in its recalcitrance to rapid microbial degradation. DOM of varying recalcitrance can be exported from the ocean surface to depth by subduction or convective mixing and oxidized over months to decades in deeper seawater. Carboxyl-rich alicyclic molecules (CRAM) are characterized as a major component of recalcitrant DOM throughout the oceanic water column. The oxidation of CRAM-like compounds may depend on specific bacterioplankton lineages with oxidative enzymes cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 151 publications
7
46
1
Order By: Relevance
“…In brainstorming these challenges, we encountered successes in confirming a pattern in DOM m/z spectra that fits one of our hypotheses (Fig. 7D), and we also identified at least one recalcitrant compound that stimulates SAR202 cell growth (36). Ongoing work in our laboratories is focused on further functional studies that test the metabolic models we propose here.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In brainstorming these challenges, we encountered successes in confirming a pattern in DOM m/z spectra that fits one of our hypotheses (Fig. 7D), and we also identified at least one recalcitrant compound that stimulates SAR202 cell growth (36). Ongoing work in our laboratories is focused on further functional studies that test the metabolic models we propose here.…”
Section: Discussionsupporting
confidence: 58%
“…Both FMNO and RHD enzymes are powerful oxidases implicated in the catabolism of resistant compounds, such as sterols and lignins. Addition of lignin, a model recalcitrant compound, has been shown in a recent study to stimulate SAR202 growth (36). The expansion of these enzyme families is proposed to have enabled SAR202 to exploit new niches defined by these DOM resources.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize sample handling and reduce the possibility of DOC contamination, this was carried out using a custom positive-pressure system that enabled subsampling without removing caps from the Biotainers. An aquarium pump pumped air through a hydrocarbon trap, which pressurized the Biotainers and displaced sample water through submerged Teflon tubing as described in Liu et al (2020). To separate copepods from the sample water, a piece of 80-µm Nytex screen was affixed to the intake end of the Teflon tube with a 1 cm piece of silicone tubing over the Nytex and Teflon tube as a collar.…”
Section: Zooplankton Excreta Production Experimentsmentioning
confidence: 99%
“…Members of the SAR202 clade of marine bacteria exhibited a maximum increase in cell abundance (Figure 5 and Supplementary Figures S2C,D) in the amended treatments at the same time when CDOM decreased. SAR202 have been estimated to account for ∼30% of all bathypelagic plankton (Morris et al, 2004;Varela et al, 2008), and studies have shown that multiple SAR202 clade genomes encode families of enzymes such as flavin-dependent monooxygenases, enolases and ring-hydroxylating dioxygenases, that may allow for the degradation of recalcitrant organic matter (Landry et al, 2017;Liu et al, 2019). As such, the ability of SAR202 to degrade lignin warrants further study.…”
Section: Taxon-specific Microbial Responsementioning
confidence: 99%